The Effectiveness of Android-Based Thematic Learning E-Modules in Increasing Student Motivation - Disa, Syaharullah; Sitti Arni; Marnia (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
The problem that occurs is that students at home more often use mobile phones to open sites such as games, cartoons, and robot videos excessively. This must be watched out for because it will increase anxiety disorders, depression, eye diseases, and decreased brain capture to receive lessons. This research aims to create an android-based thematic learning interactive e-module application in elementary schools (SD) that can help the teaching and learning process of students and teachers. This data was obtained through field research, literature research, and results from questionnaires. This research uses literature methods in data collection and for system development using DevOps methods. This application planning uses JAVA programming languages, and NonSql for its database as well as for testing this system using the Black Box method. The results of this study show that the application of e-modules is interactive thematic learning. After testing the e-module application with several parents and teachers, this application can be said to be worth using because of the 20 Respondents and the number of questions 15 showed the average results of the utility aspect which was 88 %, the ease of use aspect 88 %, and the user interface quality aspect 87 % with very feasible criteria. In addition to parents and teachers, this study was tested by a team of experts with an average result of typographic aspects of 84.5 %, visual aspects of 86 %, convenience aspects of 79 %, content feasibility aspects of 86.5 %, and learning aspects of 86.5 % with very feasible criteria.